The Effect of Differentiation Approach Developed on Gifted Students - ÖZDEMİR, AHMET ŞÜKRÜ (KAMLA-RAJ ENTERPRISES, 2015)
The aim of the paper is to determine the effect of the developed differentiation approach related to mathematics education of gifted students going to secondary school when compared with the programme of noticing individual differences applied in Science Art Centre on achievement and creative thinking skills of gifted students. In the present paper, in the scope of quantitative research, the model of pre test-post test with control group was used. The working group of the research consists of twelve 6th grade gifted students going to Science Aft Centre in Istanbul. When the experimental group to whom the activities designed based on differentiated approach were applied compared with the control group to whom the activities designed related to individual differences noticing programme were applied, achievement scores, creative thinking skills based on fluency, flexibility,. originality and elaboration scores and creative thinking skills based on curiosity, imagination, risk-taking and complexity increased in a significant way.
Keywords: Mathematics Education; Differentiation; Creativity; Achievement; Science Art Center; ACADEMIC-ACHIEVEMENT; ENRICHMENT PROGRAM; CREATIVITY; TRIAD